Effect of Epoxy Resin Reinforcement on Screw Withdrawal Strength of Fiberboard and Particleboard Used in Furniture Industry - Uysal, Mesut; Tasdemir, Cagatay; Memis, Dogan (Zagreb Univ, Fac Forestry, 2023)
The study aimed to increase the screw withdrawal strength of medium density fiberboard and particleboard used in furniture strength by using epoxy resin in the screw pilot hole. Therefore, the effects of pilot hole diameters, screw diameter, and amount of epoxy resin on screw withdrawal strength of medium density fiberboard and particleboard from face and edge were investigated. According to TS EN 13446, 50 mm x 50 mm specimens were cut from commercial medium density fiberboard and particleboard boards. A static load was applied parallel to the screw direction. The screw withdrawal strength of medium density fiberboard was higher than the screw withdrawal strength of particleboard because of its density. Besides, the screw withdrawal strength of medium density fiberboard and particleboard samples with a 3.5 mm screw diameter was higher compared to those with a 4.5 mm screw diameter. A decrease in pilot hole diameter and an increase in the amount of epoxy resin provided higher screw withdrawal strength of materials. Using 20 % epoxy resin of the volume of the pilot hole resulted in two times better screw withdrawal strength values. The study showed that a higher amount of epoxy resin, smaller pilot hole diameter, and smaller screw diameter contribute to better screw withdrawal strength of both medium density fiberboard and particleboard from the face and edge.
Keywords: epoxy resin; reinforcement; screw withdrawal strength; medium density fiberboard; particle-board